(Mis-)information technology: Internet use and perception of democracy in Africa - Joël Cariolle; Yasmine Elkhateeb; Mathilde Maurel (Fondation pour les études et recherches sur le développement international (FERDI), 2022)
This paper investigates the impact of internet use as a means of accessing news on African citizens' demand for and perception of the supply of democracy. This question is addressed using cross-sectional data from the last three rounds of the Afrobarometer survey for a sample of 25 African countries between 2011 and 2018. Using an instrumental variable approach to control for the possible endogeneity bias between internet use and citizens' perceptions, we found that using the internet to get news has a negative and significant effect on the demand for and on the perceived supply of democracy. The negative effect is channeled through two main factors.
Keywords: 330